نبوة محمد عند آنا ماري شيمل (Annemarie Schimmel) - Farhah Farhah; Ratih Ayu Muflihah Salwa; Farhan Afif Al-Kindi (Universitas Darussalam Gontor, 2020)
AbstractMuhammad in Islam is an example for all Muslims in the world. However, the Orientalist figure has a different view on the Muslims about Muhammad. In Europe, the Prophet Muhammad is seen as an idolater or renamed Mahound (The Dark Soul), known as the Anti-Christ, and a Christian who diverges from his religion. But German Orientalist Annemarie Schimmel has a different look with the most orientalist. He is a Orientalist figure who covers the love of Prophet Muhammad in depth. Seen in describing Muhammad as a worthy model of the example of people all over the world because of its tenderness, goodness, courtesy, politeness and familiarity. Annemarie Schimmel used the method of phenomenology in his research and he tended to use mystical science to adopt the notion of Islamic sufism; such as: Jalaluddin Rumi, Sana'i, Atthar and others who Mengagung-agungkan Prophet Muhammad SAW, showed sincerity and his attention to religion. His view of the Prophet Muhammad and also Muslims in general, he admitted that Muhammad was a good example and also a concluding prophet who had no messenger or other religion after his return. He also acknowledged the prophetic sign of Muhammad such as the Qur'an which was revealed to him, Isra’ Mi'raj and Mu'jizat; Like splitting the moon and her chest split in small time. And he also included the view of scholars and Muslims about the prophetic prophet especially mystical or Sufism.